Performance metrics to predict national-level competition outcomes in a cluster of road cyclists - Cesanelli, L.; Lopez, J. A. F.; Lagoute, T.; Ylaite, B.; Stasiulis, A. (International Journal of Performance Analysis in Sport, 2024)
Quantifying the pivotal elements that contribute to success in cycling and their strength, is of paramount importance in the formulation of sound and effective training regimens. Here we evaluated the power and differences of distinct performance indicators in predicting cycling competition outcomes. A total of 38 competitive male Lithuanian cyclists participated in this study, engaging in a maximal incremental exercise test, a cycling efficiency protocol, and a maximal sprint performance evaluation, from which multiple performance variables were derived. The cyclists were involved in two distinct competitions, where completion average speed and power profiles underwent analysis. Qualitative visual assessment was also employed to explore supplementary performance dimensions within these competitions. Notably, the principal explanatory variables for the two competitions were peak oxygen consumption relative to body mass (r = 0.74, p < 0.05) and cycling gross efficiency (r = 0.72, p < 0.05), respectively. Qualitative analysis unveiled divergences in terms of challenges and race dynamics inherent to the two competitions, while power profile comparisons yield no significant differences (p > 0.05). In conclusion, this study profiled Lithuanian cyclists, revealing power and differences among various performance metrics in predicting outcomes in diverse competitions. The comprehensive methodology highlighted the advantages of evaluating competition results, offering insights for improved training and tailored performance assessments.